(untitled) (CIPEEX, 2022)
FRAGILITY SYNDROME HAS BEEN DESCRIBED AS THE DECREASE OF PHYSIOLOGICAL RESERVES AND INCREASE THE VULNERABILITY OF INDIVIDUALS TO STRESSORS, REDUCING THEIR CAPACITY OF HOMEOSTATIC ADAPTATION, THAT IS, OF RESILIENCE. THE OBJECTIVE OF THIS STUDY WAS TO REPORT THE CLINICAL EVOLUTION OF AN INSTITUTIONALIZED ELDERLY PERSON IN RELATION TO THE FRAGILITY SYNDROME. AN 80-YEAR-OLD MAN RESIDING IN A LONG-TERM INSTITUTION (ILPI) IN THE MUNICIPALITY OF ANÁPOLIS SINCE 2015. THE ELDERLY PRESENT PSYCHIATRIC DISORDER (SCHIZOPHRENIA). IN 2016 THE ELDERLY WAS CONSIDERED AS PRECARIOUS, PRESENTING AUTONOMY, DESPITE THE LOW VISUAL ACUITY. ONE YEAR LATER, IT BECAME FRAGILE, WITH A CERTAIN DEGREE OF DEPENDENCE ON THE ACTIVITIES OF DAILY LIVING (ADLS). IN 2018, THE FRAILTY PERSISTED, EXISTING COMORBIDITIES WORSENED AND NEW MORBIDITIES APPEARED, SUCH AS PARKINSON’S SYNDROME AND HEARING LOSS, WHICH PROMOTED SOCIAL ISOLATION OF THE ELDERLY AS WELL AS A DEPENDENCE OF THE SAME FOR THE EXECUTION OF SGAS AND A WORSENING OF FUNCTIONAL MOBILITY OF THE ELDERLY. IT WAS OBSERVED THROUGH THIS CASE REPORT, A RAPID EMBRITTLEMENT OF THIS INSTITUTIONALIZED ELDERLY AND LOSS OF AUTONOMY. THERE IS NO INCENTIVE FOR THE PRACTICE OF PHYSICAL ACTIVITY OR THE DEVELOPMENT OF MANUAL, RECREATIONAL ACTIVITIES THAT SOCIALIZE THE ELDERLY AND CAN REDUCE THE IMPACT OF INSTITUTIONALIZATION ON THE HEALTH OF THE ELDERLY.